Pendidikan Anti Korupsi Terhadap Karakter Kedisiplinan Peserta Didik - Wahyuni, Tri; Utami, Ichwani Siti (Universitas Pamulang, 2023)
Abstract: This study aims to determine whether there is an effect of Anti-Corruption Education on the Disciplinary Character of Students at SMP Negeri 30 Tangerang. This research was conducted using a quantitative approach and the method used was correlational. The population in this study were 339 class VII students with a sample of 77 students. The data collection technique used was a questionnaire with a Likert scale questionnaire instrument. The data analysis technique used is analysis test, prerequisite test and Pearson Correlation Hypothesis Test. The results showed that the relationship between anti-corruption education variables and disciplinary character variables has a strong relationship strength and has a significant relationship (rho = 0.625; sig. = 0.000; p-value = 0.05) and the effect of anti-corruption education variables on disciplinary character variables is 39. 0% (Rsquare = 0.390) and has a significant effect (DF = 2;44, F = 48.033, sig. = 0.000, p-value = 0.05).